2022
DOI: 10.3390/jpm12122016
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Psychiatric Symptoms in the Elderly: The Role of Gender and Resilience

Abstract: COVID-19 represents an overwhelming stressor to mental health. Elderly individuals are particularly at risk, but it is still unclear whether the risk is equally distributed among men and women. The aim of this study was to define gender differences in persistent psychiatric symptoms after COVID-19 illness and to test their association with resilience factors. Methods: We assessed 348 individuals aged >65 years at a multidisciplinary post-COVID-19 service. Mood and anxiety symptoms were investigated, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Anxiety is a growing psychological disorder globally, especially in the context of the COVID-19 outbreak in the last three years ( Blasbalg et al, 2023 , Dai et al, 2022 , Janiri et al, 2022 ), and is associated with poor quality of life and disease prognosis in individuals. In addition, anxiety-based psychological disorders place a significant burden on the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is a growing psychological disorder globally, especially in the context of the COVID-19 outbreak in the last three years ( Blasbalg et al, 2023 , Dai et al, 2022 , Janiri et al, 2022 ), and is associated with poor quality of life and disease prognosis in individuals. In addition, anxiety-based psychological disorders place a significant burden on the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the prevalence of women in the group with chronic fatigue is associated with both psychological and physiological characteristics of women, such as a lower tendency to mask symptoms, as well as neurohormonal characteristics [35].…”
Section: Discussionmentioning
confidence: 99%
“…It was also revealed that resilience played a protective role among psychologically maltreated youngsters in Turkey [ 17 ]. Recently, it was found that the gender plays a role in shaping resilience [ 18 ]. In Tunisia, a recent ACE survey among youth revealed alarming rates.…”
Section: Introductionmentioning
confidence: 99%